DEGENERATIVE CHANGES IN THE MITOCHONDRIA OF FLIGHT MUSCLE FROM AGING BLOWFLIES - Sacktor, Bertram (The Rockefeller University Press, 1972)
Mitochondria from flight muscle of aging blowflies, Phormia regina, were examined morphologically and biochemically with the electron microscope. An age-dependent degeneration of the mitochondria that is characterized, in part, by the reorganization of the inner membrane into myelin-like whorls has been found. The concentric rings increase in size and number, eventually replacing the normal cristal conformation. Glycogen rosettes are frequently seen in the center of the whorl and may represent the intrusion into the mitochondria of the glycogen in the cytoplasmic matrix of the muscle. The degenerating mitochondria are not associated with lysosomal activity, as indicated by the absence of acid phosphatase. An intense acid phosphatase activity is noted, however, in the dyad, comprising elements of the T system and sarcoplasmic reticulurn. Cytochrome oxidase is active in the ultrastructurally intact portion of the mitochondrion but activity is not evident in that part of the mitochondrion that has undergone morphological change. Thus, the ultrastructural degradation of the mitochondria is correlated with a decrease in biochemical function. This suggests a correspondence between a decrease in the bioenergetic capacity of the flight muscle and a decline in the ability of the aged insect to fly.